BACTERIAL QUORUM SENSING AND ITS APPLICATION IN BIOTECHNOLOGY - S. UMESHA; SHIVAKUMAR, J. (International Journal of Pharma and Bio Sciences, 2013)
Many bacteria use small diffusible signalling molecules called Autoinducers to communicate each other termed as Quorum Sensing. The signalling molecules in gram- positive bacteria are oligopeptides, in gram- negative bacteria are N- acyl homoserine lactone and a family of auto inducers known as auto inducer- 2 in both gram- positive and gram- negative bacteria. These molecules are internalized in the cell and activate a particular set of genes in all bacterial population, the bacterial virulence which is also controlled by quorum sensing. The detection and identification of quorum sensing molecules include cell based assays using specific bacteria biosensors, Thin- layer chromatography, Liquid chromatography and Mass spectrometry. Paper strip whole cell biosensors are a novel, inexpensive and portable filter paper based strip biosensor for the detection of bacterial quorum sensing signalling molecules, N- acyl homoserine lactones. Quorum sensing in bacteria has a wide application in Biotechnology like pathogen diagnostics and therapeutics. As many of the human and plant bacterial pathogens employ the acyl homoserine lactone based quorum sensing mechanism for regulation of pathogenicity determinant synthesis or biofilm formation. The application of quorum quenching strategy may be an alternative approach for fighting these microorganisms. The acyl homoserine lactone degrading enzymes together with quorum sensing inhibitors may be successfully used to disrupt bacterial cell to cell communication and to control bacterial infections.